GASTRITIS - Сайиджанова Феруза Латифжоновна (Web of Journals Publishing, 2024)
Gastritis is one of the most common diseases of the digestive organs, accounting for 80% of stomach diseases. The frequency of the disease increases with age. According to observations in the field of gastroenterology, up to 70-90 percent of elderly patients have various pathologies.
Keywords: Gastritis, gastḗr, Helicobacter pylori, toxicoinfecsia, gastritis fibrinosa, gastritis orrosiva, gastritis phlegmonosa.